Interval appendectomy-Current perspectives-narrative review article - Dr Kumar Hari Rajah; Soma. M.Frcs; Ganesh R FRCOG (Innovative Journal of Medical and Health Sciences, 2023)
The indication of interval appendectomy afterthe management of appendicular mass has beencontroversial. There has been no consensus on the indication of interval appendectomy.The indication is usually decided by the treating surgeon, with the current trend moving towards omission of interval appendectomy in favor of follow up of patients with computerized tomography and colonoscopy. With better investigative tools the relevance of interval appendectomy is being questioned. We have conducted this review article to look at the role and relevance of interval appendectomy in the management of appendicular mass.